Organization of methodological support of the educational process in higher education - Odarich, Irina Nikolayevna; Sobakina, Tatyana Gavriilovna; Gorovoy, Sergey Alekseevich (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The creation and improvement of modern information technologies require higher education institutions to introduce new approaches to learning, ensuring the development of communicative, creative and professional knowledge, and the need for self-education. The introduction of information technology in the educational process of universities is moving to a new stage - the introduction of new multimedia educational materials. A large number of diverse information resources are being created in Russia, which have significantly improved the quality of educational and scientific activities. More and more often multimedia technologies are used in training, the spectrum of which has expanded significantly: from the creation of training programs to the development of a holistic concept for building educational programs in the field of multimedia, the formation of new learning tools. Methodically, the textbooks are structured in such a way that they meet the programs of leading universities in Europe and the requirements of a credit-modular system for organizing the educational process, which laid the foundation in our country like the ECTS system adopted in the Bologna process. The practical value lies in the fact that the textbooks allow students, bachelors, masters and graduate students of technical universities to independently master the knowledge of modern electronics. The materials of the textbook will help specialists in practice in the development, implementation and operation of electronic devices and systems, which are an integral part of electrical, radio engineering, telecommunications, computer, biomedical and other devices and complexes, technological equipment for automating technological processes, marine, space and defense equipment.